Effect of Cocoa (Theobroma cacao) Plantation Types on the Distribution of Anuran Communities in Ore, Ondo State, Nigeria - AB Onadeko (Journal of Applied Sciences and Environmental Management, 2016)
Anuran species diversity and abundance were evaluated in different farming status of cocoa plantation  in Ore, Ondo State, Nigeria. Applying the combination of visual encounter survey (VES) and acoustical survey (AES), the different farms surveyed were categorized as; 1) pure cocoa farms with pesticides applied (PCWP); 2) pure cocoa farms without pesticides application; 3) intercropped cocoa farms with pesticides applied (ICWP); and 4) intercropped cocoa farms  without pesticides application (ICNP). The surrounding primary/secondary forest (PSFV) was sampled applying the transect method. A mean total of 690±2.6 anurans belonging to 28 species, 14 genera and 9 families were recorded during the study. Out of these, 10, 19, 17, 22 and 26 species were recorded  respectively from PCWP, PCNP, ICWP, ICNP and PSFV. The anuran species richness was significantly different between the different cocoa  plantation status and the forest sites (F4, 10 = 20.55, P< 0.01). The highest mean number of  individuals (190±9.5) was observed at ICNP followed by PSFV (183±5.7), while the least was at PCWP (77±8.0). There was also significant difference (F4, 10 = 150.48, P< 0.01) between the abundance of anuran species at the various  sites. Diversity indices (Shannon and Margalef) showed that the forest sites had the greatest (3.204 and 4.799) respectively while the pesticide using pure  cocoa farms had the least (1.853 and 2.072). Generally, the result of the study clearly indicated that pesticide use cocoa farms were significantly lower  compared to other sites. Farmers are encouraged to engage in intercropping (polyculture) especially with food and economic crops in a biodiversity friendly manner which could have similar characteristics of a natural ecosystem, thereby enhancing the  biological diversity of agro-ecosystems. © JASEM